Comparative expression profiling of heat-stress tolerance associated HSP60 and GLUT-1 genes in Indian buffaloes - Singh, Ravinder; Rajesh, C; Mishra, S K; Gurao, Ankita; Vohra, Vikas; Niranjan, S K; Kataria, R S (Indian Journal of Dairy Science, 2018)
Rate of synthesis of lactose from glucose and environmental heat stress conditions are two very important key factors that govern or affect the productivity of livestock species. Buffaloes due to their dark black coat color, less effectual evaporative cooling system due to poorly developed sweat glands as well as sparse hairs on body are more susceptible to thermal distress. When heat stress is supplemented with high ambient humidity, its effect is intensified. Milk yield of buffaloes during lactation mostly depends upon the synthesis of lactose which in-turns depends on availability of glucose in mammary gland. During lactation, 85 percent of the total glucose of body utilized only by mammary glands for the milk production. In our present study we took both factors viz. heat stress and glucose transporters into consideration to analyze the expression levels of both heat shock protein (HSP60) and glucose transporter (GLUT-1) genes in Murrah buffaloes of Haryana state and compare the expression levels of these genes with Chilika & Paralakhemundi buffaloes of Odisha state. In Murrah four-fold and three-fold higher gene expression of GLUT-1 gene than Chilika (At High THI) and Paralakhemundi breed, respectively No significant change in the expression of HSP60 in Murrah buffalo as well as other two breeds of Odisha state were observed. The results indicate Odisha buffaloes to be better equipped to heat stress adaptation as well as being high yielder dairy type breed, Murrah has higher requirement of glucose transportation to cop up with higher demand of lactose.